EVOLUTIONARY DISTINCTIVENESS OF SRI LANKAN AVIFAUNA - Seneviratne, S.S. (My University, 2017)
The evolutionary history of a phylogenetically distinct group of organisms (a clade) can be traced by using a phylogenetic tree. Such phylogenetic trees can also be used to measure the amount of evolutionary history captured by each member species (node) in the tree. Evolutionary Distinctness (ED) and Evolutionary Distinct and Globally Endangered Score (EDGE) are two such vital parameters that could elucidate the phylogenetic history captured in member species. Birds evolved from a lineage led by dinosaurs over a period of ~100 million years and today the class Aves is a highly specious lineage with over 10,000 extant species. About 5% of the global avian diversity is represented in Sri Lanka with 34 endemic species. Here we quantify the evolutionary distinctness of Sri Lankan avifauna using a phylogenetic tree constructed for all the 342 bird species that are found in 71 Important Bird Areas (IBAs) of Sri Lanka. We constructed the tree from DNA sequence archives at www.birdtree.org using bioinformatics tools and higher-order phylogenetic backbones. ED and EDGE scores of all 342 birds were calculated in R Package. Batrachostomus moniliger (Ceylon Frogmouth) is the most evolutionary distinct (ED) species in Sri Lanka, while Otus thilohoffmanni (Serendib Scops-owl) is the most evolutionary distinct endangered lineage (EDGE) of the country. Harpactes fasciatus (Malabar Trogon), Pitta brachyura (Indian Pitta), Phoenicopterus roseus (Greater Flamingo) and Tachybaptus ruficollis (Little Grebe) are the rest of the top 5 species with highest ED. Centropus chlororhynchus (Green-billed Coucal), Myophonus blighi (Ceylon Whistling-thrush), Leptoptilos javanicus (Lesser Adjutant) and Pelecanus philippensis (Spot-billed Pelican) are the rest of the highest EDGE species in Sri Lanka. Members of order Charadriiformes (shorebirds, terns and gulls) in general have the lowest ED values. The species that have evolved recently and have sister or closely related species have relatively low ED. A species that has a high EDGE score is an isolated node in the phylogenetic tree and a globally threatened species. We believe that these parameters will give a novel evolutionary perspective for both wildlife managers and birders on avifauna of Sri Lanka.
Keywords: avifauna, birds, evolutionary distinctness, evolutionary distinct and globally endangered Score, Phylogeny, Sri Lanka